Avitaminosis A & dentoalveolar development disturbance - Gálvez Galla, Luis H. (2006)
Several investigations have demonstrated the adverse effects of the hypovitaminosis A in the stomatological field, characterized by ectomesenehyrnal ceIls atrophy and osteoblastic hyperactivity disordered during the phase of the embryonic development; however, the information is limited to the histological manifestations by deficiency in later stages after birth; keeping in mind that we are a country in development with nutritional problems not resolved. The present study was carried out to establish the morphological changes of the dentoalveolar complex present, after birth, for vitamin A deficiency; for which, we used 20 Holstman rats, of 21 days of age, fed with diet of lacking vitamin A, The control group, in addition received weekly one dosis of 100 U.l. of retinol at last to complete the normal dietetic balance. The histological cuts, of rat incisors with avitaminosis A, colored with hematoxilyn and eosin, obtained by conventional methods after the seven and eigth week of experimental phase, Shown in fue odontogenic base acid resistant enamel apposition which goes from 0 to 3 μ of thickness (fig.3), with cylindrical ameloblasts inhibited funcionally and in sorne cases with lost of their plasmatic union complex side conextion. Besides, it shows differentiatinn of bucal adontoblasts with reduced production of dontine matrix and absence of lingual odontoblasts (fig.3), the dental pulp next to the specialized celIs is mesenquimatic and vascularized (Fig.3). The transverse and longitudinal histological cuts of the molars crown with avitaminosis A, shown a pulpodentinary complex with lack of production of predentine, and in some cases almost unexistant. The periodontal complex shown a relative enlargement of the alveolar crest without sign of remodelation (fig.4). The morfological changes of the dentoalveolar complex existent in cases of avitaminosis A, tested with Chi Square al a level of 99% confidence is significant high (see graphics 1-7).